PAIRED READING AND APPLICATION PROCESS - Necmi AYTAN (Fırat University, 2019)
The aim of this study is to reveal the paired reading strategies and application stages. In the study field survey and document analysis methods are used, application and benefits of the paired reading strategies which is done at appropriate environment are discussed. In the application process, paired reading showes itself in two directions. The first one is mutually made as (together) paired reading like teacher-student, family member - child, strong reader-poor reader. The other one is made independent (solo) reading. While the first reading is made at the same time, at all points, in the other one critical opportunity and time is given to the reader. But during the reading teacher wants student to repeat the mistakes which are made by the student and so provides a more accurate reading. This application process is exemplified and stages are presented. It can be said that paired reading could be used in the development of reading skills through appropriate strategies and practices. With the strategies before reading during reading and after reading the stages of paired reading and a course sample is presented. In the reading process, when the level and status of reading is taken into account ıt has been concluded that paired reading is a practical method of reading.